2015
DOI: 10.1590/1516-3180.2013.8012608
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fetuses evaluated due to suspected anencephaly: a population-based cohort study in southern Brazil

Abstract: CONTEXT AND OBJECTIVE: Anencephaly is considered to be the most common type of neural tube defect.Our aim was to assess the clinical and gestational features of a cohort of fetuses with suspected anencephaly. DESIGN AND SETTING: Population-based retrospective cohort study in a referral hospital in southern Brazil. METHODS:The sample consisted of fetuses referred due to suspected anencephaly, to the Fetal Medicine Service of Hospital Materno Infantil Presidente Vargas, between January 2005 and September 2013. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It is conceivable that the dramatic presentation of an acraniate and neckless fetus with bulging eyes gives the impression of a frog, especially to ignorant lay people. Anencephalic infants, most of which are born alive and die within a day [Pelizzari et al, 2015], have been reported to show bursts of forceful, jerky and sometimes excessive movements-especially those lacking a brain stem-that are quite unlike normal fetal motion patterns [Visser et al, 1985]. Again, in the eyes of ignorants these movements may impress as attempts to crawl or fly.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the dramatic presentation of an acraniate and neckless fetus with bulging eyes gives the impression of a frog, especially to ignorant lay people. Anencephalic infants, most of which are born alive and die within a day [Pelizzari et al, 2015], have been reported to show bursts of forceful, jerky and sometimes excessive movements-especially those lacking a brain stem-that are quite unlike normal fetal motion patterns [Visser et al, 1985]. Again, in the eyes of ignorants these movements may impress as attempts to crawl or fly.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is without final opinion (PL 5,069/13) for religious reasons that defend the unborn child's right. This conduct is an important step in the feminist view and, if passed, will be a gain for women's right to their choices in society (17) . However, it must be observed that the public network offers the first ultrasound from 17 to 22 weeks of gestation, thus leaving the stipulated period for the procedure, in case any abnormality is found incompatible with life.…”
Section: Discussionmentioning
confidence: 99%
“…Even female infant gender is cited as a risk factor, as most of the anencephalic fetuses are females [16]. Anencephaly was also associated with chromosomal abnormalities, such as Edwards syndrome -trisomy 18 [14]. Also, studies show that many of the anencephalic fetuses present associated abnormalities, such as spina bifida, cleft palate, clubbed foot, clubbed hands and gastroschisis, suggesting the overwhelming presence of genetics in the neural tube defects [18].…”
Section: R J M Ementioning
confidence: 99%
“…Also, studies show that many of the anencephalic fetuses present associated abnormalities, such as spina bifida, cleft palate, clubbed foot, clubbed hands and gastroschisis, suggesting the overwhelming presence of genetics in the neural tube defects [18]. These aspects highlight the importance of genetic factors in the etiopathogenetics of neural tube defects [11,14,15]. Hence, this is the reason why over the last few years, more and more studies have assessed the involvement of genetic and additional nongenetic risk factors in the development of anencephaly [16].…”
Section: R J M Ementioning
confidence: 99%